2000
DOI: 10.1034/j.1600-0773.2000.pto860207.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis by Lovastatin through Activation of Caspase‐3 and DNase II in Leukaemia HL‐60 Cells

Abstract: Lovastatin, an HMG-CoA reductase inhibitor, was found to suppress growth and induce apoptosis in culture human promyelocytic leukaemic cell, HL-60. However, the mechanisms of lovastatin-induced apoptosis are still unclear. In this study, we attempted to elucidate the signal transduction pathway for lovastatin-induced apoptosis in HL-60 cells in a dose-and time-dependent manner. The features of this apoptosis were attenuated by the presence of mevalonate, a metabolic intermediate of cholesterol synthesis. Treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Cyt, cytochrome c; FPP, farnesyl pyrophosphate; GGPP, geranylgeranyl pyrophosphate; p21 wAF1/CIP1 and p27…”
Section: Antitumor Effects Of Statins In Clinical Studiesmentioning
confidence: 99%
“…(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Cyt, cytochrome c; FPP, farnesyl pyrophosphate; GGPP, geranylgeranyl pyrophosphate; p21 wAF1/CIP1 and p27…”
Section: Antitumor Effects Of Statins In Clinical Studiesmentioning
confidence: 99%
“…Statins can also activate caspase proteases involved in programmed cell death. Lovastatin induced apoptosis in leukemia and prostatic cancer cells through activation of caspase-7 and caspase-3, respectively (Marcelli et al, 1998;Wang et al, 2000a) and cerivastatin caused cell death in human myeloma tumor cells by activating caspase-3, caspase-8, and caspase-9 (Cafforio et al, 2005). Frick et al (2003) reported multiple statin effects on blood vessel formation by inhibition of angiogenesis through down-regulation of proangiogenic factors, such as VEGF, inhibition of endothelial cell proliferation, and block of adhesion to extracellular matrix.…”
Section: A Effects Of Statins In Cancermentioning
confidence: 99%
“…Cafforio et al showed that cerivastatin caused cell death in human myeloma tumor cells by activating caspase-3, caspase-8, and caspase-9 [80]. Similarly, lovastatin induces apoptosis in prostatic epithelium and leukemia cells through activation of caspase-3 and caspase-7, respectively [81,82].…”
Section: Induction Of Apoptosismentioning
confidence: 99%